PERBEDAAN PREVALENSI DEPRESI PADA KO-ASISTEN FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA DAN KO-ASISTEN FAKULTAS KEDOKTERAN UNIVERSITAS WARMADEWA - Luh Made Mustikayanthi Devi; Ni Ketut Sri Diniari (Universitas Udayana, 2016)
Depression is a psychiatric disorder most frequently encountered and the most common cause of morbidity and mortality compared with other psychiatric disorders. The physical and mental burden on medical students is quite heavy, because they must undergo preclinical studies along with hospital duties as a co-assistant. This constant disruption may have a tendency to cause depression. The purpose of this study was to determine the prevalence differences of depressive disorders in two co-assistant groups who have different external environments. This study is a descriptive analytic cross sectional approach undertaken in Denpasar Sanglah Hospital and Sanjiwani Hospital in February-March 2016 on medical students from two different universities. Data were collected using common questionnaires, Lie-Minnesota Multiphasic Personality Inventory (L-MMPI) and Beck’s Depression Inventory (BDI). Then the prevalence of depressive disorders was calculated in each group and the data analyzed by independent t-test. Total respondents of this study amounted to 68 people, each of 34 people in each group. The prevalence of depression of each of the 34 respondents was 35% (12 people) on a Udayana University co-assistant and by 32% (11 people) on a Warmadewa University co-assistant. With independent t-test results obtained p = 0.801 (p> 0.05) for a score of depression in Udayana University co-assistant and Warmadewa University co-assistant. The results show the value of p = 1.0 (p> 0.05) between the Udayana University co-assistant men and women, as well as the value of p = 0.285 (p> 0.05) between the Warmadewa University co-assistant men and women. The prevalence of depression in Udayana University co-assistant was 35% and 32% in Warmadewa University co-assistant. There was no significant difference between the average incidence of depression in Udayana University co-assistant and Warmadewa University co-assistant. It was also found that there was no significant relationship between the level of depression by gender.